ACTIVITIES OF THE CHINESE ASSOCIATION OF HARMONICA IN SHANGHAI, RELATED TO ACCORDION - Huang, In (E-Journal VFU, 2025)
Before 1949, the accordion activities in Shanghai are practiced mostly in relation to harmonica performances. Amidst these activities, the Chinese association of Harmonica, founded by Wang Qingxun, not only advertises and popularizes the harmonica but also contributes a lot for the encouraging and development of the accordion in China.
Keywords: Chinese Association of Harmonica; accordion; performance